Answer:
x = 3 or x = 2 or x = -1 or x = -5
Step-by-step explanation:
Solve for x:
((x - 3) (x - 2) (x + 1) (x + 5))/x = 0
Multiply both sides by x:
(x - 3) (x - 2) (x + 1) (x + 5) = 0
Split into four equations:
x - 3 = 0 or x - 2 = 0 or x + 1 = 0 or x + 5 = 0
Add 3 to both sides:
x = 3 or x - 2 = 0 or x + 1 = 0 or x + 5 = 0
Add 2 to both sides:
x = 3 or x = 2 or x + 1 = 0 or x + 5 = 0
Subtract 1 from both sides:
x = 3 or x = 2 or x = -1 or x + 5 = 0
Subtract 5 from both sides:
Answer: x = 3 or x = 2 or x = -1 or x = -5
Answer:It would be -4 across and go two up
Step-by-step explanation:
Answer:
The bottom one (D) the end it is sitting on
Step-by-step explanation:
what's there to explain xD
To construct a circle that circumscribes to a triangle, you would have to construct a circle that where all vertices of the triangle are on the circle. To do this you would have to construct the perpendicular bisectors of each side with your compass and straight edge. Comment on this answer if you are unsure of how to construct a perpendicular bisect (it's a long fundamental process to describe, and I wouldn't want to lecture you one something you already know). Once you have done so, set your compass point on the point where all perpendicular bisectors intersect (they should intersect in ONE point, if not you will have to redo it). Set your other compass lead on one of the vertices and spin away! If you have done this correctly, you should hit all three vertices when spinning your compass. Hope this helps!
Fun fact: the point where all perpendicular bisectors intersect is called the circumcenter
Answer:
1.)
≈ 3.652
2.) I would say something about how the A in front of cos in the equation would change to 90, rather than stay 75 (in the equation for the step by step), but it would be easier to just use the Pythagorean theorem.
Step-by-step explanation:
I think we may have the same class so hopefully this helps:
1.)
--> law of cosines formula.
--> plugged in numbers; when you draw the triangle, the included angle would be A, and the opposite side would be a. B and b, and C and c are opposite each other. In this case, a is the hypotenuse.
--> in between steps.
--> more simplifying.
--> answer
2.) This one is just an explanation: The 75 in the equation is the given angle, which is a. If this changes, it would just change in the equation too. And obviously, if it's 90 degrees, you can just use Pythagorean theorem a^2+b^2=c^2.
Good luck! :)